2017
DOI: 10.3233/bmr-169630
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic neck pain on cervical joint position error (JPE): Comparison between young and elderly subjects

Abstract: Cervical joint position sense is impaired in subjects with chronic neck pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…These improvements are perhaps that placebo tape also may have produced mechanical effects that could decrease pain. Considering that the application of Kinesio™ tape was improper, even though it was applied to the cervical muscles, it could have provided sensory feedback during neck movements, thereby decreasing mechanical irritation of soft tissues [ 34 36 ]. There may be another explanation: a strong relationship between neck pain intensity and cervical proprioception in participants with neck pain [ 37 ], considering that increased pain intensity impairs cervical proprioception and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…These improvements are perhaps that placebo tape also may have produced mechanical effects that could decrease pain. Considering that the application of Kinesio™ tape was improper, even though it was applied to the cervical muscles, it could have provided sensory feedback during neck movements, thereby decreasing mechanical irritation of soft tissues [ 34 36 ]. There may be another explanation: a strong relationship between neck pain intensity and cervical proprioception in participants with neck pain [ 37 ], considering that increased pain intensity impairs cervical proprioception and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested changing the proprioception of the neck to account for their findings. Alahmari et al [81] compared the JPE of 42 patients with chronic neck pain and 42 age-matched healthy people, and found that the patients had a greater error in all movement directions tested (p \ 0.001). Similarly, other studies have revealed a significant greater error in patients with chronic idiopathic neck pain when compared with asymptomatic controls, despite the variability in methods used in these studies [68,[82][83][84][85][86][87].…”
Section: Jpe Testmentioning
confidence: 99%
“…Previous studies have found that subjects with CS have abnormal joint position error (JPE); this was measured by an active target relocation test in which the subject relocates the head to a target previously determined by the examiner [7,8]. The reasons for proprioceptive impairments are degeneration and abnormal afferent inputs by the muscles and joint receptors to the higher centers [9][10][11][12]. Within and surrounding the joint, neuromuscular control can be disturbed by impaired kinesthesia that places the joint at risk of injury or trauma by the muscles producing unbalanced torque [13,14].…”
Section: Introductionmentioning
confidence: 99%